WRITTEN CORRECTIVE FEEDBACK ON EFL STUDENTS AT AN ISLAMIC JUNIOR HIGH SCHOOL - Eka Mareta Suharyanti; Endang Fauziati (Universitas Bengkulu, 2020)
Teachers provide students with corrective feedback for guiding them in the process of teaching a language. This study aimed to investigate the types of corrective feedback that the teacher used in teaching writing recount text, this also employed to reveal the students' motivation for writing recount texts, and to explore the benefit of teacher corrective feedback to the students' ability in writing recount text at Manbaul Huda Islamic Junior High School Central Java Indonesia. Descriptive qualitative method was employed by interviewing both the teacher and the second-year students. The participants were three teachers and twenty students. There were three guided Interview questions for teachers and two questions for students. The findings of this study turned out that the teacher employed indirect corrective feedback and gave symbols to the student’s error production. Most of the students are highly motivated to be able to write a status on Facebook or other online media by using English. The most important advantage of obtaining corrective feedback for the students is to understand the use of grammar in making a sentence. This study concluded that the motivation of the students to write recount text was to get teacher corrective feedback to be able to write the appropriate sentence and to increase their ability in writing English. This also implied that different types of corrective feedback might impact differently to the students in improving their motivation to learn English more.